Acral, superficial spreading melanoma arising on melanocytic nevus in a pregnant woman: A case report with review - Sunil Kumar Gupta; Ajay Kumar; Vivek Gupta; Alpna Thakur (Wolters Kluwer Medknow Publications, 2015)
We are reporting a case of superficial spreading melanoma (SSM) on left palm of a 37-year-old pregnant housewife. She had a small acquired melanocytic nevus on her left palm since childhood, which changed its consistency and color in the last 4 months. Dermoscopy of the lesion indicated malignant changes. The lesion was managed surgically using split-thickness skin graft. The histopathology report was suggestive of SSM with positive HMB-45 cells. SSM is very rare on the acral site, and it is very difficult to differentiate it from acral lentiginous melanoma. The rarity of the site (acral nonchronic sun damage) with evolution during pregnancy and importance of management approach are reasons for publishing this case.